In-Hospital Outcome Of Acute Coronary Syndrome In Patients With Diabetes Mellitus (University Heart Journal, 2009)
Diabetes mellitus adversely influences the outcome of acute coronary syndrome. This study evaluated the in-hospital outcome of acute coronary syndrome in patients with diabetes mellitus. In this prospective observation study 130 patients with acute coronary syndrome were enrolled. They were divided into diabetic and nondiabetic group. Diabetic patients were taken as case and nondiabetic patients as control. Outcome parameter studied were in-hospital mortality, cardiogenic shock, congestive heart failure, different arrhythmias and recurrent angina. In this study, one third (32%) of the patients were diabetic with mean age 58±10.0 years vs. 53.0±13.6 years in diabetic and nondiabetic group, respectively. Majority of the patients in both groups were male. Congestive heart failure and arrhythmias were more common in case group compared to those in control group (19% vs. 13.6% p=0.424; 23.8% vs. 13.6%, p= 0.148, respectively). Cardiogenic shock developed in 7.1% of diabetic patients and 8% of nondiabetic patients. In hospital mortality was 7.1% and 5.7% in diabetic and nondiabetic group, respectively. Recurrent angina developed only in diabetic patients. Therefore, diabetic patients with acute coronary syndrome encountered more in- hospital adverse outcome.   doi: 10.3329/uhj.v5i1.3437 University Heart Journal Vol. 5, No. 1, January 2009 24-27